Geoblocking and geopricing: An analysis in the light of Mike Feintuck’s public interest theory - Guimarães, Marcelo Cesar (Law, State and Telecommunications Review, 2019)
Purpose ”“ This study aims to demonstrate that companies are not free to operate in the e-commerce field, notably with regard to geoblocking and geopricing practices, since they must duly respect constitutional economic order principles. Methodology/approach/design ”“ The methodology of the paper is based on Mike Feintuck’s public interest theory, according to which there are values beyond those of market economics that should be preserved, often to the detriment of private interests. Furthermore, the Decolar.com case is used as an empirical case study. Findings ”“ It has been identified that geoblocking and geopricing practices can effectively violate constitutional principles and that consumer and antitrust microsystems can suppress those conducts, shaping the performance of economic agents to the public interest. Practical implications ”“ The results of this article indicate that consumer and competition agencies can act more actively to curb the harmful geoblocking and geopricing practices.